Glucose index and chemical composition of rice cultivars and their effect on type 2 mellitus diabetes - Dhuha M. Al-Atbi; Nawfal Alhelfi; Abbas A. Mansour (Zien Journals, 2023)
Rice is the staple food and energy source for half of the world's population; thus, it has great nutrition and, at the same time, health effects. Rice is generally considered a food with a high glycemic index (GI). However, this depends on the cultivar, textural and processing factors. As a significant contributor to the population's increased glycemic load when rice is consumed, there is growing concern that the high prevalence of insulin resistance results from consuming large amounts of rice. Therefore, devising ways and means to reduce the effect of rice on blood sugar is imperative. This review compiles studies examining the glucose index of rice products. Tables of the chemical composition of rice are also included. Rice elicits a relatively large glycemic response and is associated with exacerbating glucose intolerance. This contributes to an increase in the glucose load (GL) of diets in countries where it is the main ingredient due to the large amount eaten and the increase in its population index in these countries where an increase in diabetes rates has been observed
Keywords: Brown rice; basmati rice; glucose index